Oilseeds as a Perspective in the Nutrition on Dairy Farm - Agnes Suli; Bela Beri; János Csapo; Elizabet Berecz (Scientific Papers Animal Science and Biotechnologies, 2023)
In the last decades many researches were made to change the milk product food’s composition. The production of better fat-compound milk and dairy products became a goal in the name of health conscious nutrition. Our researches were motivated by non-adequate milk fat’s compound. With the optimal supplement of the feed can be increased the proportion of the polyunsaturated fatty acids and can decreased the unsaturated fatty acids. The object of our experiment to study the effect of natural-based feed additives, such as oilseeds (whole linseed, extruded linseed, whole rapeseed) on the fatty acid composition of milk fat. Further information was gained about of oilseeds in specific amounts to be fitted into technology of an intensive dairy farm in practice. The feed supplements were whole, untreated rapeseed and linseed and cold extruded linseed as a part of total mixed ration. The level of the processing of feed supplements affected the fatty acid composition of milk fat. The effect of full fat linseed feed supplement was more significant than that of the cold extruded linseed, in the increase of the polyunsaturated fatty acids, with special regard to the increase of the α-linolenic acid proportion. Out of the full fat oilseeds the feeding of full fat rapeseed did not result in a considerable change in the fatty acid composition of milk fat. After applying full fat linseed as feed supplement, the proportion of α-linolenic acid, a conjugated linoleic acid, an eicosadienoic acid and a docosapentaenoic acid increased in the fatty acid composition of milk fat, while the concentration of many saturated fatty acids reduced.